2002
DOI: 10.2527/2002.80102747x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc source (zinc oxide vs zinc proteinate) and level on performance, carcass characteristics, and immune response of growing and finishing steers

Abstract: Sixty Angus and Angus x Hereford steers (246 kg initial BW) were used to determine the effects of Zn level and source on performance, immune response, and carcass characteristics of growing and finishing steers. Treatments consisted of 1) control (no supplemental Zn), 2) ZnO, 3) Zn proteinate-A (ZnProt-A, 10% Zn), and 4) ZnProt-B (15% Zn). Treatments 2, 3, and 4 supplied 25 mg of supplemental Zn/kg diet. Steers were individually fed a corn silage-based diet during the 84-d growing phase and a high corn diet du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
81
1
11

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 16 publications
14
81
1
11
Order By: Relevance
“…Notice that in the current study the ZnSO 4 was supplied as a topdressing, and this method can, in part, guarantee the consumption of sufficient amounts of Zn. Likewise, Spears and Kegley (2002) reported increased ADG in growing steers when a diet with 33 mg Zn/kg DM was supplemented with 25 mg Zn/kg DM inorganic sources. On the other hand, Froetschel et al (1990) showed that high concentration of Zn affects the number of protozoa, and Zn supplementation decreases ruminal digestion of dietary amino acid, thereby increases CP's reach to small intestine.…”
Section: Adg and G:fmentioning
confidence: 99%
“…Notice that in the current study the ZnSO 4 was supplied as a topdressing, and this method can, in part, guarantee the consumption of sufficient amounts of Zn. Likewise, Spears and Kegley (2002) reported increased ADG in growing steers when a diet with 33 mg Zn/kg DM was supplemented with 25 mg Zn/kg DM inorganic sources. On the other hand, Froetschel et al (1990) showed that high concentration of Zn affects the number of protozoa, and Zn supplementation decreases ruminal digestion of dietary amino acid, thereby increases CP's reach to small intestine.…”
Section: Adg and G:fmentioning
confidence: 99%
“…Carcass characteristics were not affected (P 0.05) by ZM, but interactions (Table 3) indicated that bulls fed ZH plus ZM had the lowest (P B0.01) backfat thickness and IMF. Previous studies evaluated ZM effects on IMF thickness and backfat thickness in steers, but not the interaction ZH )ZM (Greene et al 1988;Malcom-Callis et al 2000;Spears and Kegley 2002). Zinc has a lipogenic effect (Tang and Shay 2001;Park et al 2003;Vardatsikos et al 2013) caused by inhibition of lipolytic substances (May and Contoreggi 1982;Oh and Choi 2004) and by changing expression of transcript factors and genes responsible for triglycerides and lipoproteins synthesis (Oh and Choi 2004).…”
Section: Carcass Characteristicsmentioning
confidence: 99%
“…Zinc has been related to several mechanisms, such as being a lipogenic compound (Malcom-Callis et al 2000;Oh and Choi 2004), stimulating lipogenesis and inhibiting lipolysis (Coulston and Dandona 1980;May and Contoreggi 1982) through insulin signaling (May and Contoreggi 1982;Saltiel and Kahn 2001;Eom et al 2001;Park et al 2003). Adding Zn to diets favors the deposition of fat and the degree of marbling in meat of feedlot cattle (Greene et al 1988;Spears and Kegley 2002). Adding organic Zn produces better results than inorganic sources (MalcomCallis et al 2000;Spears and Kegley 2002;Nunnery et al 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the most common forms of supplementation is the ionic (chlorides, sulfates, oxides, hydroxides, carbonates). However, some of these sources of minerals, especially trace elements, have low absorption in the animal organism or low bioavailability (Spears, 1996).…”
Section: Introductionmentioning
confidence: 99%